QoS performance analysis of non-slotted and slotted optical burst switched networks - Coulibaly, Y. (Institute of Electrical and Electronics Engineers Inc., 2016)
The need for large-bandwidth networks is in continuous growth. Such demands are attributed to the user desire to have everything on-line. To support needs, all-optical networks, with their large bandwidth lend themselves considerable attention from both industry and academia. As a result, some optical switching paradigms have been proposed such as optical circuit switching, optical packet switching and optical burst switching. Among these paradigms, Optical Burst Switching (OBS) is seen as a viable solution. However, lack of mature optical memory makes burst loss ratio in OBS critical which needs to be solved before OBS can really be used in telecommunication networks. Many solutions have been proposed and evaluated to address this issue. These solutions can be categorised into two categories: architectural solutions and procedural solutions. Architectural solutions deal with the architectural design of OBS and these solutions are further classified into two classes: non-slotted and slotted OBS. Procedural solutions deal with the improvement of the operation of OBS networks in terms of burst assembly, routing, switching, scheduling, signalling, etc. In this paper, we focus on architectural solutions where we investigate QoS performance of non-slotted and slotted OBS in terms of burst loss ratio and throughput. Simulation results show that slotted outperforms non-slotted OBS; the results also demonstrate that higher priority bursts outperforms lower priority ones.